1995
DOI: 10.2307/1511202
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Effectiveness of Speech Recognition on the Written Composition Performance of Postsecondary Students with Learning Disabilities

Abstract: Seventeen males and twelve females wrote essays under three conditions: (a) without assistance; (b) using a human transcriber; and (c) using a speech recognition system. Students received higher holistic scores using speech recognition than when writing without assistance at a statistically significant level ( p=.048). In order to determine the reasons for the superior scores on the essays written using speech recognition, 22 measures of fluency, vocabulary and syntax were computed. Several measures showed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 26 publications
5
70
0
2
Order By: Relevance
“…Instead of relying on another person, speech recognition systems take the burden off of using human transcribers and allow students to independently dictate work (Higgins & Raskind, 1995). Hux, Rankin-Erickson, Manasse, and Lauritzen, (2000) and Rosen and Yampolsky (2000) discussed that due to motor constraints, the hands-free speech recognition system is attractive.…”
Section: Speech Recognition Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead of relying on another person, speech recognition systems take the burden off of using human transcribers and allow students to independently dictate work (Higgins & Raskind, 1995). Hux, Rankin-Erickson, Manasse, and Lauritzen, (2000) and Rosen and Yampolsky (2000) discussed that due to motor constraints, the hands-free speech recognition system is attractive.…”
Section: Speech Recognition Systemsmentioning
confidence: 99%
“…A number of studies indicated the importance or rehearsal and planning prior to composing using dictation (De La Paz & Graham, 1997;Higgins & Raskind 1995;Wetzel, 1996) because participants in these studies improved writing skills through dictation only when planning first. In the studies, all students with learning disabilities had difficulty handwriting, spelling, punctuating, and with rate of production.…”
Section: Description Of Speech Recognition Software Speech Recognitimentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in classrooms where teachers had very little experience with software the computer would be used for 'educational' games that had little to do with the overall language program. Higgins and Raskind (1995) and Wepner (2004) have argued that the literature has overemphasised the technical concerns such as graphics and sound, to the detriment of addressing educational concerns about content, processes and opportunities for learning.…”
Section: Over the Past 20 Years Schools Have Spent Millions Of Dollamentioning
confidence: 99%